Perbandingan Ungkapan Cinta dalam Bahasa Indonesia dan Turki pada Lagu “Apalah Cinta” Karya Ayu Ting Ting - Badrika Syawal Insani; Neng Dini Agustin (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This research discusses the comparison of expressions of love in Indonesian and Turkish in the song "Apalah Cinta" by Ayu Ting Ting, which is the result of a cross-cultural collaboration with the Turkish singer, Keremcem. This song is interesting to analyze because it reflects the cultural and linguistic differences between the two languages ​​in expressing love. This research uses a text analysis approach to examine song lyrics in both languages, and considers the cultural context that influences expressions of love. The research results show that Indonesian tends to convey love in a direct and simple way, while Turkish uses more poetic and metaphorical expressions. Even though there are differences in language structure and style of expression, they both have a similar message, namely about the beauty of love and universal feelings that transcend language and cultural boundaries. This research highlights how works of art such as songs can be an effective medium for bridging cultural differences, as well as enriching cross-cultural understanding.